Blockchain based examination system for effective evaluation and maintenance of examination records - Acharya, Rahul; Binu, Sumitra (International Journal of Engineering and Technology, 2018)
The main objective of this paper is to provide a Blockchain based framework for conducting and evaluating academic tests in a peer-to-peer manner with auto-generation of certificates upon successful completion of the examination. We illustrate how a self-sustained education ecosystem can be developed on top of a blockchain for a fair evaluation without the need of a central trusted entity for obtaining certificates or degrees that prove one's dexterity over a subject. In order to make the test as transparent as possible, we store the hash-digest of every question asked and every question answered, directly on the blockchain. This facilitates the tracing of how exactly a candidate received the score that he/she received, adding more credibility to the obtained certificate.Â Â